El fenómeno de El Niño en Guatemala - Barrios Pérez, Camilo; Montes, Carlo (2024)
This study delves into the effects of the El Niño phenomenon in Guatemala, focusing on its consequences for the country's overall agroclimatic conditions. El Niño, characterized by the warming of waters in the central and eastern equatorial Pacific Ocean, triggers disruptions in global climatic patterns.